Gingival Reactive Lesions in Orally Rehabilitated Patients by Free Revascularized Flap. (12th August 2018) - Tenore, Gianluca; Mohsen, Ahmed; Pompa, Giorgio; Brauner, Edoardo; Cassoni, Andrea; Valentini, Valentino; Polimeni, Antonella; Romeo, Umberto
Abstract : The aim is to discuss four cases of gingival reactive hyperplastic lesions in patients with a history of excision of oral neoplastic lesions and rehabilitation by a free revascularized flap of the iliac crest. One female and 3 male patients were referred due to the presence of exophytic lesions at the rehabilitated sites. The clinical examination revealed that the poor oral hygiene was the common trigger factor in all the cases, in addition to trauma from the upper left second molar in the first case, pericoronitis related to a partially erupted lower right third molar in the third case, and poor stability of an upper removable partial denture in the fourth case. All the cases were subjected to elimination of these suspected triggering factors, exclusion of dysplasia, excisional biopsy by CO2 laser, and five follow-up visits. The histological examination of all the cases confirmed the diagnosis of pyogenic granuloma. These presented cases suggest that the limitations in oral functions and maintaining the oral hygiene measures following the free revascularized flap reconstruction surgery probably played a role in the development of gingival reactive hyperplastic lesions with presence of trigger factors such as local trauma, chronic infection, or inadequate prosthesis.